Perlindungan Hukum Terhadap Direksi Atas Keputusan Bisnisnya Sesuai Prinsip Business Judgement Rule - Doni Damara Eko Prasetyo; Muhammad Badrus Salam Robieth As Syadili; Yulianingsih Yulianingsih (Fakultas Hukum Universitas Islam Malang, 2023)
The purpose of this study is to determine the existence of the business judgment rule in Indonesia so that it can be used as a reference in protecting directors for the business decisions they make. This type of research is normative juridical with a statutory, case, and conceptual approach. The result of this study is that the principle of business judgment rule provides protection for directors. This principle is regulated in Article 97 Paragraph (5) of Law Number 40 of 2007 concerning Limited Liability Companies, so that based on this article if it is fulfilled cumulatively by the directors, the directors can be released from all responsibilities and get legal protection from the business judgment rule principle given to himself for the business decisions he made.